EVALUATION SUITE FOR UZBEK SPEECH AND BILINGUAL TRANSLATION AT SCALE (American Journal of Research in Humanities and Social Sciences, 2025)
In this article we present a reproducible evaluation suite for Uzbek speech and bilingual translation at scale. It unifies ASR, TTS, MT, and speech-to-text evaluation across Latin/Cyrillic scripts, dialectal variation, and code-switching. We provide task-specific metrics, error taxonomies and human protocols, and we report baseline scores and reliability to support fair, longitudinal benchmarking.